Phenotypic Definition of the Progenitor Cells with Erythroid Differentiation Potential Present in Human Adult Blood - Valentina Tirelli; Barbara Ghinassi; Anna Rita Migliaccio; Carolyn Whitsett; Francesca Masiello; Massimo Sanchez; Giovanni Migliaccio (Stem Cells International)
In Human Erythroid Massive Amplification (HEMA) cultures, AB mononuclear cells (MNC) generate 1-log more erythroid cells (EBs) than the corresponding CD34pos cells, suggesting that MNC may also contain CD34neg HPC. To clarify the phenotype of AB HPC which generate EBs in these cultures, flow cytometric profiling for CD34/CD36 expression, followed by isolation and functional characterization (colony-forming-ability in semisolid-media and fold-increase in HEMA) were performed. Four populations with erythroid differentiation potential were identified: CD34posCD36neg (0.1%); (barely detectable-0.1%); (2%) and (75%). In semisolid-media, cells generated BFU-E and CFU-GM (in a 1 : 1 ratio), cells mostly BFU-E (87%) and and CD34negCD36low cells were not tested due to low numbers. Under HEMA conditions, CD34posCD36neg, CD34posCD36pos, CD34negCD36low and CD34negCD36neg cells generated EBs with fold-increases of ≈9,000, 100, 60 and 1, respectively, and maturation times (day with >10% CD36highCD235ahigh cells) of 10–7 days. Pyrenocytes were generated only by CD34neg/CD36neg cells by day 15. These results confirm that the majority of HPC in AB express CD34 but identify additional CD34neg populations with erythroid differentiation potential which, based on differences in fold-increase and maturation times, may represent a hierarchy of HPC present in AB.